E-book readers: Handy tools for agricultural extension workers in Ethiopia? - Mekonnen, Fanos; Hoekstra, Dirk; Gebremedhin, Berhanu; Bogale, A. (2016)
Especially in remote rural areas, using information and communication tools in agricultural extension makes sense. The International Livestock Research Institute in Ethiopia has tested e-book readers with regard to their practicality.